NASCITA E DIFFUSIONE DELLA QUESTIONE ALIMENTARE URBANA IN FRANCIA - Caroline Brand (Bollettino della Società Geografica Italiana)
This article intends to outline the key features of the urban food issue emergence at the local authorities scale. France is well-known across the world as a country where food matters but surprisingly, France was almost absent of the first debates of the North-American and European food planning community. Though, food issues are recently reinvested through the notion of «food governance» whose breeding ground was the periurban agriculture issue. This emergence is particularly analyzed from the scope of the Terres en Villes network, leader of the first debates. The first paths of the urban food issue aimed at comforting the periurban agriculture position in an urbanization context. This initial agricultural prism is evolving toward an agri-food perspective. Progressively, the agricultural prism is opening toward other silos and in particular to the consumers. Nonetheless, the red thread of the food policy is not reached yet. Difficulties subsist in going beyond the initial agricultural prism. The city food supply issue dominates and leaves out the other dimensions of the urban food issue. France is characterized by the existence of several arenas seizing one facet of the food issue and their concrete connection stands still. Even if the «food governance» term is largely diffused since 2012, there is a gap between the pioneer of food governance conceptualization and the reality of apprehension of the food issue by the local authorities.